2014
DOI: 10.1080/10852352.2014.881180
|View full text |Cite
|
Sign up to set email alerts
|

NuFit: Nutrition and Fitness CBPR Program Evaluation

Abstract: The present study combines community-based participatory research (CBPR) and peer education to create NuFit, a nutrition and fitness curriculum, adapted by community and student peer leaders for Latino and African-American high-school students in Chicago. The purpose of this pilot study was to assess the feasibility and efficacy of the NuFit curriculum to improve the knowledge, attitudes, and behaviors regarding nutrition and fitness for minority and adolescent student populations. The NuFit curriculum improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…As identified through these studies, adolescent girls prefer interaction and collaboration with their peer networks thus, including this education with all adolescents and parent groups, may be beneficial (McKinney et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Ten of the 40 studies [20,23,26,29,39,40,44,46,51,53] lacked a clear description of the randomization process, but the effect sizes were comparable for both categories in the total group. A clear description of when the process of randomization occurred before or after the baseline assessment was lacking in 29 studies [16e18, 20,21,23,24,26,28e31,33e37,39,41,42,44,46e 48,51e55].…”
Section: Risk Of Biasmentioning
confidence: 99%